A Long-Term Comparison of Presenting Characteristics of Children with Newly Diagnosed Type 1 Diabetes Before and During the COVID-19 Pandemic - Gülay Kaya; Emine Ayça Cimbek; Osman Yeşilbaş; Yusuf Emre Bostan; Gülay Karagüzel (Galenos Yayincilik, 2022)
INTRODUCTION: Diabetic ketoacidosis (DKA) - a potentially preventable complication of type 1 diabetes mellitus (T1D) - is one of the most common chronic childhood diseases, and is associated with a significant risk of morbidity and mortality. The limited use of healthcare services due to fear of Coronavirus disease-2019 (COVID-19) transmission during the pandemic has raised concerns of delays in T1D diagnosis, among other diseases. This study investigated the presenting characteristics of newly diagnosed T1D patients assessed in a single clinic during the pandemic and compares them with the pre-pandemic period. METHODS: For the purpose of this study, the first year of the pandemic is referred to as the 'pandemic period', and the previous three years as the 'pre-pandemic period'. Patient files were reviewed retrospectively, the demographic and clinical characteristics and laboratory findings of the patients were recorded, and the findings from both periods were compared. RESULTS: The number of patients diagnosed with T1D in the pandemic period was 44, and in the pre-pandemic period 39 in 2017, 22 in 2018 and 18 in 2019. The two groups had similar age, sex, pubertal stage and anthropometric characteristics (p>0.05). Regarding the type of presentation, the frequency of DKA was significantly higher in the pandemic period (68.2%) than in the pre-pandemic period (40.5%) (p=0.006), and this difference was also observed in the comparison by years (p=0.016). The duration of symptoms (16.5+-10.7 vs. 23.5+-17.6 days) and the length of hospital stay (10+-3.9 vs. 15.2+-5.5 days) were significantly shorter in the pandemic period (p=0.032, and p<0.001, respectively). There was no difference in the frequency of severe DKA between the pandemic (46.7%) and the pre-pandemic (37.5%) periods (p>0.05). However, pH (7.17+-0.16 vs. 7.26+-0.14) and bicarbonate (12.8+-6.3 vs. 16.6+-6.3) levels were significantly lower in the pandemic period (p<0.005). Additional signs of infection on admission were less frequent in the pandemic period (9.1%) than in the pre-pandemic period (27.8%) (p=0.027). The groups did not differ in terms of hemoglobin A1c, C-peptide, concurrent thyroid autoantibodies and tissue transglutaminase antibodies (p>0.05). The rate of anti-glutamic acid decarboxylase positivity was higher in the pandemic period (73.8% vs. 39.2%) (p=0.001) while the frequency of other diabetes-associated autoantibodies was similar between the groups (p>0.05). The polymerase chain reaction test for COVID-19 was negative in six patients with a history of contact. DISCUSSION AND CONCLUSION: There was an increased frequency and severity of DKA in children with newly diagnosed T1D in the pandemic period, and these findings justify concerns related to the diagnosis of other diseases during the pandemic. Studies to raise awareness of diabetes symptoms during the pandemic should be continued regularly to reach all segments of society. Our study provides an additional contribution to the literature in its coverage of the one-year period during the pandemic and its comparison with the previous three years.